2019
DOI: 10.1007/s12369-019-00599-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Mistreatment and Emotional Capability Following Aggressive Treatment of Robots and Computers

Abstract: Robots (and computers) are increasingly being used in scenarios where they interact socially with people. How people react to these agents is telling about the perceived empathy of such agents. Mistreatment of robots (or computers) by co-workers might provoke such telling reactions. This study examines perceived mistreatment directed towards a robot in comparison to a computer. This will provide some understanding of how people feel about robots in collaborative social settings. We conducted a two by two betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…When asked why they refused to hit the ServBot or felt uncomfortable doing it, participants answered that they felt an emotional connection with the ServBot that refrained from hurting it (Riddoch and Cross 2021 ). Customers also do not perceive a ServBot as a simple machine but as a social agent through emotional capacity and anthropomorphic features (Carlson et al 2019 ). When witnessing the mistreatment of a ServBot versus a computer, customers showed significantly more empathy for the ServBot (Carlson et al 2019 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 99%
“…When asked why they refused to hit the ServBot or felt uncomfortable doing it, participants answered that they felt an emotional connection with the ServBot that refrained from hurting it (Riddoch and Cross 2021 ). Customers also do not perceive a ServBot as a simple machine but as a social agent through emotional capacity and anthropomorphic features (Carlson et al 2019 ). When witnessing the mistreatment of a ServBot versus a computer, customers showed significantly more empathy for the ServBot (Carlson et al 2019 ).…”
Section: Servbots' Capacity To Use Ij During Service Recovery: a Comp...mentioning
confidence: 99%
“…Despite believing this, we often engage with agents—such as social robots— as if they are acting intentionally, 12 or as if they are experiencing. Regardless of whether (or not) participants explicitly believe a social robot possesses mental states, intentions, or experiences, humans often seem to engage with them as if they do, going so far as to feel bad for them when they are “suffering” ( Bartneck and Hu, 2008 ; Darling et al, 2015 ; Seo et al, 2015 ; Carlson et al, 2019 ; ). If it is the case that intending and willing are a form of experiencing, then we can see that robotic actions which are perceived as intentional are perceived as originating from an experiencing Other—for, as Scheler wrote, “…we cannot be aware of an experience without being aware of a self…” ( Scheler and Health, 1923 , p. 9).…”
Section: Robot Moral Standingmentioning
confidence: 99%
“…Studies on human-robot interaction analyzed the empathy in two dimensions: "human to robot" and "robot to human" (Kerruish, 2021;Paiva et al, 2004;Nomura, 2018). Studies conducted with children and adults and investigated the human-to-robot dimension revealed that humans were empathic towards the robots (Carlson et al, 2019;Darling et al, 2015;Mattiasi et al, 2019;Riek et al, 2009;Suzuki et al, 2015, Seo et al, 2018Küster et al, 2020). Rosenthal-von der Pütten et al ( 2013) allowed the subjects to watch two different video images of a zoomorphic robot Pleo in an empirical study conducted with 41 participants.…”
Section: Social Robots and Empathy: Can Robots Empathize?mentioning
confidence: 99%